Financing Models based on Waqf Money through Investment - Syofi Aruni Mafaza; Khoirul Umam; Suyoto Arief; Setiawan bin Lahuri (Institute for Research and Community Empowerment (LPPM TAZKIA), 2020)
Islamic microfinance institutions can apply the potential of cash waqf optimally and effectively for a better economic impact on the targeted levels of society. This study explores the opinions and recommendations of various researchers on the model of integration of cash waqf as financing in Islamic microfinance institutions. This study uses qualitative methods by reviewing previous kinds of literature. This research uses qualitative methods that only discuss the cash waqf model as financing through investment. The result of this study is that cash waqf can be used as financing in Islamic microfinance institutions, provided that the assets of the property should not be reduced in the slightest. Therefore, in anticipation of the reduced waqf of money used as a source of financing funds, Islamic financial institutions must guarantee the funds through various means such as takaful, Islamic investment, Islamic bank deposits, and other institutions in accordance with Islamic principles. Using cash waqf as a source of financing funds in Islamic microfinance institutions will reduce the level of difficulty of micro-entrepreneurs in obtaining business financing. Also, the benefits of cash waqf investment itself will be distributed to the people in needs of goods, services, health facilities, education, mosques, etc.